Farmer’s Awareness Regarding Climate Change and its Effect on Ground Water - R M Gupta; A Negi; P Sharma; S Kaur (Indian Journal of Extension Education, 2025)
The growing impacts of extreme weather events due to climatic variations have already been felt throughout the world. Be it incessant rains, floods, long droughts, extreme heat, wildfires, etc., the impacts are visible across the globe affecting the lives and professions in many ways. Agriculture is one of the severely hit areas due to climatic variations. In light of such events, it has become imperative to study the environmental awareness of the farmers and their agricultural practices. The present study was carried out in 2023 in randomly selected five villages namely from two randomly selected blocks of Ludhiana, Punjab. From each village a sample of 25 farmers was selected randomly comprising a total of 125 respondents. The data was collected through a survey using the questionnaire. Percentages and mean were used to analyze the data. The findings revealed that the respondents were aware of climate change and its repercussions but they were not always following water-saving practices in their fields. Suggested creation of awareness and educating farmers regarding various technologies to save groundwater. Extension functionaries should work to sensitize farmers to mitigate climate change.